Rebranding American men's heritage fashions through the use of visual merchandising, symbolic props and masculine iconic memes historically found in popular culture. Issue 1 (1st October 2013) - Matthews, Kevin; Hancock, II, Joseph H.; Gu, Zhaohui
This article takes a critical examination of how merchandising inspired by popular culture communicates various notions of history, and in this case, to display and sell heritage fashion lines. In specific retail locations popular and historically cultural-influenced visual displays and aesthetic merchandising strategies are studied to ascertain and interpret the importance of visual display as one vehicle of fashion branding. A careful interpretive analysis, determines that retailers associate cultural-influenced thematic props and icons reflective of America culture to sell men's mass-fashion garments and give them an aura of authenticity and American heritage. These displays and the branding stories convey conceptual (pop) cultural masculine icons or noted historical memes of US historical masculine imagery that include such male icons as the rebel, the cowboy, the Ivy Leaguer, jocks and blue-collar workers, revealing how these worn styles have infused into American culture and men's mass fashion as contemporary street style.